Identifikasi Jenis Elemen Lanskap dan Serangga Hama pada Taman di PT Bali Agung Sesari - Marsianus Tena; I Wayan Dirgayana; Dewa Ayu Ari Febriyanti; Jeromi Bulu Mila; Putu Surya Anggaraditya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to identify landscape elements, namely softscape and hardscape, and to determine the types of insect pests found in the garden of PT Bali Agung Sesari. The research was conducted in Ungasan Village, South Kuta District, Badung Regency, Bali, from 1 february to 2 April 2026. The method used was descriptive qualitative with quantitative data support through observation, interviews, and documentation. The results showed that the softscape elements consisted of yellow iris (Trimezia martinicensis), heliconia (Heliconia psittacorum), and purple leaf (Graptophyllum pictum), while the hardscape elements included paving blocks and boundary walls. The insect pests identified were the white-marked tussock caterpillar (Orgyia leucostigma) and moth caterpillars (Lymantria), which attacked the leaves of yellow iris plants. Out of 150 observed plants, 115 were infested, resulting in a 76.67% attack rate. Pest attacks caused leaf damage and reduced the aesthetic value of the garden. Pest control was carried out mechanically by manually removing pests and pruning damaged plant parts. In conclusion, the presence of pests affects plant conditions, indicating the need for more effective and sustainable pest management.